Evaluation of the toxicological safety and anti-inflammatory effects of Folium syringae powder using in vivo models - Lv, Fengxia; Li, Pan; Wang, Bin; Yuan, Xiaobing; Wang, Xu; Dong, Shishan (Frontiers in Veterinary Science, 2025)
Folium syringae (DXY), a widely used traditional Chinese medicinal component, can be used as an alternative for the reduction of veterinary antibiotic use. But few studies have explored its anti-inflammatory effects and toxicological safety. This study aimed to evaluate the anti-inflammatory effects and acute and subacute toxicity of orally administered DXY powder in mouse and rat models, respectively. The anti-inflammatory effect was evaluated by comparing the intensity of edema and granuloma to that induced by Macleaya cordata extract (positive control). The toxicological effects were evaluated by assessing clinical signs, body weight, food intake, water consumption, blood biochemical and hematological parameters, organ coefficients, and organ histopathology in the treated rats. Oral administration of DXY powder in once-daily doses of 0.32 and 0.64 g/kg/day for 7 consecutive days effectively prevented xylene-induced ear edema in mice compared with the normal control group. In the acute and subacute toxicity evaluations, no clinical signs of toxicity, mortality, and no adverse effects on the target organs were observed. No significant pathological changes in any organs or tissues were observed at a daily dose of 3.0 g/kg for 6 consecutive months. However, significant pathological changes were observed in heart, liver, kidney, and intestinal tissues from the DXY powder-treated rats following daily doses of 12.0 and 48.0 g/kg for 6 consecutive months. Further studies are needed to determine whether these effects are toxic and reversible. The effective anti-inflammatory dose is far below the toxicity threshold. This study lays the foundation for the safety of DXY powder to justify its use as feed additives in veterinary clinical use.